KOMITMEN ANGGOTA ORGANISASI TERHADAP KEGIATAN ORGANISASI REMAJA MESJID DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI - Audhina Meilanie Linggawati; Daeng Ayub Natuna; Titi Maemunaty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The formulation of the research problem is how high the commitment of organizational members to the activities of youth mosque organizations in Tebing Tinggi District, Meranti Islands Regency. Then the purpose of this study was to determine the level of commitment of organizational members to the activities of youth mosque organizations in Tebing Tinggi District, Meranti Islands Regency. This research is descriptive with a quantitative approach that aims to describe the results of research with numbers. The sampling technique used a proportional stratified random sampling technique, namely sampling used when members of the population are not homogeneous consisting of homogeneous or stratified groups proportionally (Sugiyono, 2012: 93) the percentage of member commitment to the activities of mosque youth organizations in Tebing Tinggi District, Islands Regency Meranti as a whole from the first indicator of affective commitment which states Very Often (SS) 38%, Often (S) 36%, Sometimes (KK) 18%, Rarely (J) 8%, Never (TP) 0%. The second indicator is continuance commitment which states Very Often (SS) 36%, Often (S) 39%, Sometimes (KK) 15%, Rarely (J) 10%, Never (TP) 0%. The third indicator is normative commitment which states Very Often (SS) 29%, Often (S) 43%, Sometimes (KK) 11%, Rarely (J) 17%, Never (TP) 0%. From the overall average of 3 percentage indicators (SS+S) 73%, the commitment of members to the activities of mosque youth organizations in Tebing Tinggi District, Meranti Islands Regency is relatively high. Based on these results, it can be concluded that the commitment of members to the activities of mosque youth organizations in Tebing Tinggi District, Meranti Islands Regency is relatively high. The highest indicator lies in continuance commitment, with a percentage value (SS+S) of 75%.Key Words: Organizational Commitment